(untitled) (Italian Journal of Public Health, 2010)
Background: Growing medical evidence shows that access to the natural environment improves health and wellbeing, prevents disease and helps people recover from illness. Experiencing nature in the outdoors can help tackle obesity and coronary heart disease. Green areas exert their benefits on both physical and mental health, promoting physical activity and strengthening the sense of community thus positively influencing social interaction. Urbanization poses problems through effects such as environmental pollution, accidents, heat island effects, climate change and a consequent demand for urban green areas. Material and methods: We performed literature searches of electronic journal databases for studies and reviews that focused on the relationship between green spaces and health. We looked at the effects on physical health, mental health, social health, physical activity and well-being in its broadest sense and then we categorically organized our findings. Results: We found many contradictory and unexpected results. However, the reported findings were generally consistent and supported the current view that urban design and the availability of urban green spaces are key elements of prosperity and individual/collective comfort, so as to influence both the perceived health and the objective physical conditions in a measurable way. A weak relationship between physical activity levels and green space availability is observed. Conclusions: The occasionally contradictory results that emerged in this study suggest that a population’s response to urban design interventions is often unpredictable. Further research is needed to quantify the strength of relation between green spaces and urban health, but also to investigate the social and behavioural aspects which are more difficult to measure and understand.